Examination of Efficiency Based on Air Gap and Characteristic Impedance Variations for Magnetic Resonance Coupling Wireless Energy Transfer - Agcal, Ali; Bekiroglu, Nur; Ozcira, Selin (KOREAN MAGNETICS SOC, 2015)
In this paper wireless power transmission system based on magnetic resonance coupling circuit was carried out. With the research objectives based on the mutual coupling model, mathematical expressions of optimal coupling coefficients are examined. Equivalent circuit parameters are calculated by Maxwell software, and the equivalent circuit was solved by Matlab software. The power transfer efficiency of the system was derived by using the electrical parameters of the equivalent circuit. System efficiency was analyzed depending on the different air gap values for various characteristic impedances. Hence, magnetic resonance coupling,involves. creating a resonance and transferring the power without radiating electromagnetic waves. As the air gap between the coils increased the coupling between the coils were weakened. The impedance of circuit varied as the air gap changed, affecting the power transfer efficiency.
Keywords: wireless power transfer; magnetic coupling; characteristic impedance; efficiency; POWER TRANSFER; Materials Science; Physics